A new species of Bhutanthera (Orchidaceae; Orchidoideae) from Nepal - Raskoti, Bhakta Bahadur (Phytotaxa, 2012)
Bhutanthera fimbriata is described and illustrated from Nepal; diagnostic characters used to distinguish it from allied species are provided.